2018
DOI: 10.1002/2211-5463.12438
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic compressive loading activates angiotensin II type 1 receptor in articular chondrocytes and stimulates hypertrophic differentiation through a G‐protein‐dependent pathway

Abstract: Angiotensin II type 1 receptor ( AT 1R) appears to have a mechanosensing function in a number of cell types. The purpose of this study was to examine whether AT 1R expressed in articular chondrocytes is involved in osteoarthritis (OA) progression in vivo and whether cyclic compressive loading activates the AT 1R and stimulates hypertrophic differentiation of chondrocytes in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…However, a recent study found agonist-independent mechanical-induced AT 1 R activation [30] , [47] . Several groups showed that the expression of AT 1 R and AT 2 R genes is detectable in chondrocytes [82] , [83] , and we have shown that CCN2 is increased at mRNA and protein levels by treatment with ANGII (Nishida et al, unpublished data). Additionally, we have also shown that ANGII-induced phosphorylation of p38 is decreased by pretreatment with losartan, which is a specific blocker of AT 1 R (Nishida et al, unpublished data).…”
Section: Role Of Ccn2 As a Pivotal Regulator Of Mechanical Stress Resmentioning
confidence: 67%
“…However, a recent study found agonist-independent mechanical-induced AT 1 R activation [30] , [47] . Several groups showed that the expression of AT 1 R and AT 2 R genes is detectable in chondrocytes [82] , [83] , and we have shown that CCN2 is increased at mRNA and protein levels by treatment with ANGII (Nishida et al, unpublished data). Additionally, we have also shown that ANGII-induced phosphorylation of p38 is decreased by pretreatment with losartan, which is a specific blocker of AT 1 R (Nishida et al, unpublished data).…”
Section: Role Of Ccn2 As a Pivotal Regulator Of Mechanical Stress Resmentioning
confidence: 67%
“…subjected bovine cartilage chondrocyte-seeded agarose constructs to cyclic compressive load. Results showed that compressive loading up-regulated the expression of type X collagen and runt-related transcription factor 2, indicating the increased population of hypertrophic differentiated chondrocytes in the cartilage [ 93 ]. Activation of phosphorylation of c-Jun N-terminal kinase (JNK), Src, and STAT1 was also observed in chondrocytes subjected to altered functional load [ 93 ].…”
Section: The Challenges Of Articular Cartilage Regeneration In Obesitmentioning
confidence: 99%
“…Results showed that compressive loading up-regulated the expression of type X collagen and runt-related transcription factor 2, indicating the increased population of hypertrophic differentiated chondrocytes in the cartilage [ 93 ]. Activation of phosphorylation of c-Jun N-terminal kinase (JNK), Src, and STAT1 was also observed in chondrocytes subjected to altered functional load [ 93 ]. Abnormal mechanical loading alters cellular biochemical activities through stimulation of mechanoreceptors on the surface of chondrocytes that regulate cartilage remodelling and turnover, eventually resulting in cartilage breakdown [ 94 ].…”
Section: The Challenges Of Articular Cartilage Regeneration In Obesitmentioning
confidence: 99%
“… 15 Angiotensin II is a known potent proinflammatory mediator, 16 and angiotensin receptor blockers show anti-inflammatory effects in animal models of arthritis. 17 Further, articular chondrocyte angiotensin II type 1 receptor was implicated in KOA progression in a mechanical stress mouse model 18 and activation of the renin-angiotensin system might be involved in the pathogenesis of this condition. 12 Nonetheless, the association between angiotensin-converting enzyme and KOA remains controversial.…”
Section: Introductionmentioning
confidence: 99%